Mycoplasma bovis-associated verminous pneumonia in alpine chamois (Rupicapra rupicapra) - Bullone, Michela; Divari, Sara; Sereno, Alessandra; Bassano, Bruno; Gelmetti, Daniela; Gibelli, Lucia Rita; Pregel, Paola; Bollo, Enrico; Scaglione, Frine Eleonora (Frontiers in Veterinary Science, 2024)
Pneumonia is a common disease affecting Alpine chamois. However, little is known concerning the etiological agents involved. We investigated whether Mycoplasma spp. infection occurs in Alpine chamois and describe the microscopic lesions associated with Mycoplasma-associated bronchopneumonia in this species. Lung tissues obtained from 45 chamois with gross evidence of pneumonia were analysed. The histological lesions and the presence of lungworms within the lungs were evaluated blindly. The presence of Mycoplasma spp. was assessed by immunohistochemistry (Mycoplasma bovis and Mycoplasma mycoides subsp. mycoides) and by end-point PCR. M. bovis was detected by immunohistochemistry and confirmed by PCR and sequencing in 6/45 (13%) cases, while all lungs were negative for M. mycoides subsp. mycoides. A significant association was found between the detection of M. bovis and the presence of severe lungworms infection in the examined lungs. We report for the first time M. bovis as a bacteria associated with verminous pneumonia in chamois.